Functional constipation is associated with alterations in thalamo‐limbic/parietal structural connectivity. Issue 12 (19th October 2020) - Zhang, Zhida; Hu, Yang; Lv, Ganggang; Wang, Jia; He, Yang; Zhang, Lei; Li, Hao; von Deneen, Karen M.; Wang, Huaning; Duan, Shijun; Zhang, Junwang; Hou, Qiuqiu; et al.
Abstract: Background: Functional constipation (FCon) is a common functional gastrointestinal disorder (FGID) with a high prevalence in clinical practice. Previous studies have identified that FCon is associated with functional and structural alterations in the primary brain regions involved in emotional arousal processing, sensory processing, somatic/motor‐control, and self‐referential processing. However, whether FCon is associated with abnormal structural connectivity (SC) among these brain regions remains unclear. Methods: We selected the brain regions with functional and structural abnormalities as seed regions and employed diffusion tensor imaging (DTI) with probabilistic tractography to investigate SC changes in 29 patients with FCon and 31 healthy controls (HC). Key Results: Results showed lower fractional anisotropy (FA) in the fibers connecting the thalamus, a region involved in sensory processing, with the amygdala (AMY), hippocampal gyrus (HIPP), precentral (PreCen) and postcentral gyrus (PostCen), supplementary motor area (SMA) and precuneus in patients with FCon compared with HC. FCon had higher mean diffusivity (MD) and radial diffusivity (RD) in the thalamus connected to the AMY and HIPP. In addition, FCon had significantly increased RD of the thalamus‐SMA tract. Sensation of incomplete evacuation was negatively correlated with FA of the thalamus‐PostCen and thalamus‐HIPP tracts, and there was a negative correlation between difficulty of defecation and FA of the thalamus‐SMA tract. Conclusions and Inferences: These findings reflected that FCon is associated with alterations in SC between the thalamus and limbic/parietal cortex, highlighting the integrative role of the thalamus in brain structural network. Abstract : Previous studies have identified that functional constipation (FCon) is associated with functional and structural alterations in the primary brain regions involved in emotional arousal processing, sensory processing, somatic/motor‐control and self‐referential processing. However, whether FCon is associated with abnormal structural connectivity (SC) among these brain regions remains unclear. In the current study, we selected the brain regions with functional and structural abnormalities as seed regions and selected the thalamus as a seed region and used the other regions as target regions to perform the probabilistic tractography to investigate SC changes in patients with FCon and healthy controls (HC). Our results showed alterations in SC between the thalamus and limbic/parietal cortex (red line) in patients with FCon compared with HC, reflecting that FCon is associated with alterations in thalamo‐limbic/parietal structural connectivity and highlighting the integrative role of the thalamus in brain structural network.